2021
DOI: 10.15252/embj.2020106922
|View full text |Cite
|
Sign up to set email alerts
|

Sealing holes in cellular membranes

Abstract: The compartmentalization of eukaryotic cells, which is essential for their viability and functions, is ensured by single or double bilayer membranes that separate the cell from the exterior and form boundaries between the cell's organelles and the cytosol. Nascent nuclear envelopes and autophagosomes, which both are enveloped by double membranes, need to be sealed during the late stage of their biogenesis. On the other hand, the integrity of cellular membranes such as the plasma membrane, lysosomes and the nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 105 publications
(143 reference statements)
2
66
1
1
Order By: Relevance
“…Studies of membrane repair-related processes are still the subject of intensive work, in particular to elucidate the mechanism(s) that take place depending on the cell type and the nature of the damage. Many reviews already exist on this topic [ 1 , 2 , 7 , 21 , 22 , 23 ]; here, we will focus on current understanding of membrane repair mechanisms in skeletal muscle cell.…”
Section: The Sarcolemma Repair Machinerymentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of membrane repair-related processes are still the subject of intensive work, in particular to elucidate the mechanism(s) that take place depending on the cell type and the nature of the damage. Many reviews already exist on this topic [ 1 , 2 , 7 , 21 , 22 , 23 ]; here, we will focus on current understanding of membrane repair mechanisms in skeletal muscle cell.…”
Section: The Sarcolemma Repair Machinerymentioning
confidence: 99%
“…Membrane ruptures induced by mechanical stress, such as contraction, stretching, or shearing, compromise cellular homeostasis and lead to cell death in the absence of fast resealing [ 1 , 2 ]. Frequency of cell membrane disruption is high in mammal tissues subjected to severe mechanical constraints, such as cardiac or skeletal muscle, epithelia, and endothelium [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies also showed that autophagosomes can correctly seal in the absence of Atg8-PE, which does not support the role of Atg8-PE in the closure of autophagosomal membranes [52][53][54]. Recently, several studies have shown that the endosomal sorting complexes required for transport (ESCRT) machinery plays a pivotal role in the closure of autophagosomal membranes [55][56][57][58]. Using the HaloTag-LC3 autophagosome completion assays, Takahashi et al found that ESCRT-III component CHMP2A traffics to the phagophore and promotes the separation of the inner and outer autophagosomal membranes, which eventually leads to the formation of sealed autophagosomes [59].…”
Section: Autophagosome Formation and Atg8/lc3 Scaffolds As Platforms For Receptor Cargo Recruitmentmentioning
confidence: 98%
“…This series of protein complexes includes the ESCRTs-0, -I and -II, ubiquitin-binding complexes, which sequester ubiquitylated cargo and then pass it to ESCRT-III ( Frankel and Audhya, 2018 ; Henne et al, 2011 ; Piper et al, 2014 ). ESCRT-III is a generic membrane curvature-inducing polymer that combines with the downstream AAA ATPase VPS4 (VPS4A and VPS4B forms in mammals) to drive reverse topology membrane scission ( Gatta and Carlton, 2019 ; Henne et al, 2013 ; McCullough et al, 2018 ; Pfitzner et al, 2021 ; Remec Pavlin and Hurley, 2020 ; Zhen et al, 2021 ), and thus at the MVB completes ILV formation ( Raiborg and Stenmark, 2009 ; Vietri et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%